Knowing the Son - Dye, Colin W.; (1953-...) (U.K., 2008)
Most Christians appreciate what Jesus has done for them but spend little time thinking about who their Saviour is. 'Knowing the Son' explores the mystery of the fully divine, fully human nature of Jesus. It shows you how He is the Son, so that we could also become sons and daughters. It equips you to release Christians who fully understand their position as sons and daughters.
Keywords: Pentecostal churches -- Doctrines